2018
DOI: 10.4274/atfm.69875
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Systemic Disease on the Benign Paroxismal Positional Vertigo Attacks

Abstract: The aim of this study was to investigate the distribution of posterior canal benign paroxysmal positional vertigo (Pc BPPV) according to age and genders, which is the most common cause of peripheric vertigo. And also, to reveal the frequency of accompanying systemic diseases in this patient group and the any relationship of these systemic diseases on recurrent attacks. Materials and Methods: The present study is performed with 72 patients aged 21-83 years who applied to our clinic complain of peripheric vertig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition, it was stated in the study that most of these studies were conducted in Asia, and it would be wrong to generalise to the world. Akkoca et al (7) reported that recurrent attacks were more common in patients with hypertension, with 72 BPPV patients in their study. They did not find a significant relationship between DM and other comorbidities and BPPV attacks.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, it was stated in the study that most of these studies were conducted in Asia, and it would be wrong to generalise to the world. Akkoca et al (7) reported that recurrent attacks were more common in patients with hypertension, with 72 BPPV patients in their study. They did not find a significant relationship between DM and other comorbidities and BPPV attacks.…”
Section: Discussionmentioning
confidence: 77%